2021
DOI: 10.2147/tacg.s320778
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing for Aneuploidy in Patients Who Have Had Multiple Miscarriages: A Review of Current Literature

Abstract: Recurrent pregnancy loss (RPL) is an obstetrical complication that affects about 3% of reproductive age couples. Genetic and non-genetic causes of RPL are multiple; however, aneuploidy is the most common obstetrical complication that can explain single and recurrent pregnancy loss (present in about 60% of recognized clinical pregnancies which result in a miscarriage). Parental karyotyping will only be of potential benefit for 2 to 5 percentage of RPL couples who are translocation carriers. Products of concepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
(129 reference statements)
1
11
0
Order By: Relevance
“…Chromosome analysis of both couples with recurrent pregnancy loss (RPL) and products of conception (POC) is most informative in the investigation of possible genetic causes of RPL (Papas and Kutteh, 2021). Parental karyotyping can detect translocation carriers in 2-5% of RPL couples (Papas and Kutteh, 2021), while POC can demonstrate chromosomal anomalies in half of the cases. In the present issue, a new stepwise molecular work-up to diagnose chromosomal abnormalities in women who have had one or more early pregnancy losses was reported (Pauta et al).…”
Section: Editorial On the Research Topic Emerging New Tests And Their Impact Upon The Practice Of Reproductive Geneticsmentioning
confidence: 99%
“…Chromosome analysis of both couples with recurrent pregnancy loss (RPL) and products of conception (POC) is most informative in the investigation of possible genetic causes of RPL (Papas and Kutteh, 2021). Parental karyotyping can detect translocation carriers in 2-5% of RPL couples (Papas and Kutteh, 2021), while POC can demonstrate chromosomal anomalies in half of the cases. In the present issue, a new stepwise molecular work-up to diagnose chromosomal abnormalities in women who have had one or more early pregnancy losses was reported (Pauta et al).…”
Section: Editorial On the Research Topic Emerging New Tests And Their Impact Upon The Practice Of Reproductive Geneticsmentioning
confidence: 99%
“…Previous studies have demonstrated that CMA could identify chromosome anomalies in approximately 60% of POC cases from individuals with a single or recurrent pregnancy loss (Dahdouh & Kutteh, 2021; Smits et al., 2020). However, given that POC testing recommendations vary by professional organizations, a broad study of POCs with varying reasons is uncommon (Papas & Kutteh, 2021; Schilit et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR/Cas9-associated anomalies at the on-target site have been observed in human and mouse CRISPR/Cas9 microinjected embryos, and include large scale deletions, complete loss of whole and chromosomal segments, and loss of heterozygosity [ 32 , 34 , 35 , 84 ]. Embryonic loss of whole chromosomes is particularly a concern as aneuploidy has been associated with implantation failure and miscarriage in humans [ 85 ]. Neither the incidence of chromosomal loss and segmentation in CRISPR/Cas9 microinjected embryos, nor the impact of CRISPR/Cas9 induced chromosomal anomalies on developmental trajectory to the blastocyst stage or pregnancy have been extensively explored in NHPs.…”
Section: Introductionmentioning
confidence: 99%